Retrieval of crop variables with field-based X-band microwave remote sensing of ladyfinger - Prasad R. (My University, 2025)
Modeling in agriculture has been widely used to retrieve and monitor various soil and crop growth variables. Remote sensing, especially radar sensors can be useful for temporal and spatial monitoring of the soil and plant variables. Therefore, in this paper field measurements of crop ladyfinger were carried out to examine the dependency of radar backscatter on crop-soil variables and to develop a method for monitoring and retrieving crop variables for ladyfinger. A crop-bed was prepared to observe scatterometer response in the angular range of incidence angle 20-70° at 9.89 GHz in the X-band for VV- and HH-polarization. At the same time, soil moisture, plant height, leaf area index and aboveground biomass were measured at various growth stages of crop ladyfinger. The angular variation of scattering coefficient decreases with the age of crop ladyfinger shows the dominance of crop effect on soil moisture effect at the older age. Thus, angular trends are more flat as the plant grows since the effects of soil is masked by developing vegetation. Scattering coefficient increases with the increase of leaf area index for both polarizations (i.e. VV- and HH-). It was found that leaf area index and aboveground biomass of crop ladyfinger are highly correlated with microwave frequency more than with plant height and soil moisture. Leaf area index and biomass of ladyfinger crop were retrieved by polarization based model and non-linear least square optimization model. These two models gave very good results for the retrieval of leaf area index and aboveground biomass. © 2009 COSPAR.